"F" is for fugitive [compact disc, unabridged] : a Kinsey Millhone mystery - Grafton, Sue (Grafton, Sue. Kinsey Millhone mysteries., 1994)
Bailey Fowler, a confessed murderer, escaped from prison 16 years ago. Now, by sheer chance, the cops stumble on him--and a case long dead comes murderously back to life. Royce Fowler's son's reappearance gives Royce a last chance to heal an old wound. And Kinsey Millhone gets to help ... though it nearly costs Kinsey her life!